The Effect of the Implementation of Good Governance on Village Financial Management (Study on Villages in Tolinggula District, North Gorontalo Regency) - Nurjannah K. Paca; Harun Blongkod; Surya Handrisusanto Ahmad (International Journal of Economics Studies, 2026)
Village financial management is an important aspect in supporting development at the local level. The implementation of Good Governance, which includes transparency, accountability, and community participation, is a key factor in creating effective and efficient financial management. This study aims to analyze the influence of the implementation of Good Governance on village financial management in Tolinggula District, North Gorontalo Regency. The method used in this study is a quantitative approach with causal design. Data was collected through a questionnaire distributed to 140 respondents, consisting of village officials who are responsible for village financial management. The analysis technique used is Structural Equation Modeling (SEM) to test the relationship between Good Governance variables and village financial management. The results of the study show that the implementation of Good Governance has a significant influence on the effectiveness of village financial management. Transparency has the most dominant impact, followed by accountability and community participation. However, there are still challenges in implementation, such as imbalances between planning and budget realization, which lead to surpluses in some villages and deficits in others. In addition, villages with independent and developed status tend to have a better financial management system than developing villages. Therefore, efforts are needed to increase transparency, strengthen accountability mechanisms, and increase public participation in budget supervision. Thus, the implementation of more optimal Good Governance is expected to increase the effectiveness of village financial management and support more sustainable development.